EFEKTIVITAS KOMPRES SERAI DAN JAHE HANGAT TERHADAP NYERI ARTHRITIS GOUT PADA LANSIA - Awaluddin Awaluddin; Mila Asmarita (Jurnal Keperawatan Abdurrab, 2025)
Gout arthritis is a musculoskeletal disease that causes joint pain. There are many therapies available to relieve pain in patients with gout arthritis. One of them is a warm compress of lemongrass and ginger which aims to stimulate the surface of the skin to relieve pain. The purpose of this study was to determine the effectiveness of warm lemongrass and warm ginger compresses on gout arthritis pain in the elderly. The research design used is quantitative research with a quasi-experimental method with a pre-test post-test design research design. This research was carried out on May 04 – 11, 2024. The population in this study is gout arthritis patients in the working area of the Simpang Tiga Health Center, as many as 140 people and a sample of 36 people divided into 2 groups of 18 people with warm lemongrass compress intervention and 18 people with warm ginger compress intervention. The number of samples is determined using Federer's formula. The sampling technique uses purposive sampling. The data collection tool uses observation sheets and interviews. From the results of this study, it can be interpreted that there is a difference between the two intervention groups, namely warm ginger compresses are more effective in reducing pain than warm lemongrass compresses. It is recommended for the Simpang Tiga Health Center to be a source of information about herbal/complementary medicines for people with gout arthritis and its treatment so that the public can know about herbal medicines that are beneficial to health.